A Global Survey of COVID-19 Vaccine Acceptance Among Healthcare Workers - Noushad, Mohammed; Rastam, Samer; Nassani, Mohammad Zakaria; Al-Saqqaf, Inas Shakeeb; Hussain, Mudassir; Yaroko, Ali Ango; Arshad, Mohammed; Kirfi, Abdullahi Musa; Koppolu, Pradeep; Niazi, Fayez Hussain; Elkandow, Ali; Darwish, Mahmoud; et al. (Frontiers in Public Health, 2022)
Objectives: Even though several effective vaccines are available to combat the COVID-19 pandemic, wide disparities in vaccine distribution, and vaccine acceptance rates between high- and low-income countries appear to be major threats toward achieving population immunity. Our global exploratory study aims to inform policymakers on factors affecting COVID-19 vaccine acceptance among healthcare workers (HCWs) in twelve countries, based on income index. We also looked for possible predictors of vaccine acceptance among the study sample. Methods: A structured questionnaire prepared after consultation with experts in the field and guided by the ‘Report of the SAGE working group on vaccine hesitancy’ was administered among 2953 HCWs. Upon obtaining informed consent, apart from demographic information, we collected information on trust in vaccines and health authorities, and agreement to accept a COVID-19 vaccine. Results: Although 69% of the participants agreed to accept a vaccine, there was high heterogeneity in agreement between HCWs in L-LMICs and UM-HICs, with acceptance rates of 62% and 75% respectively. Potential predictors of vaccine acceptance included being male, 50 years of age or older, resident of an UM-HIC, updating self about COVID-19 vaccines, greater disease severity perception, greater anxiety of contracting COVID-19 and concern about side effects of vaccines. Conclusions: The low COVID-19 vaccine acceptance rates in low-income countries in the African continent warrants implementation of country specific public health strategies with the collaboration of the government, World Health Organization and non-governmental organizations. However, the greater threat of vaccine inequality should be tackled simultaneously.